PENERAPAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MATERI TEKANAN ZAT CAIR - Eka Amanda Febriani; Dyah Astriani; Ahmad Qosyim (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
The purpose of this study was to increase students' motivation and learning outcomes on the material of liquid pressure using animated video media. This research was a pre-experimental design research with the design of